2015
DOI: 10.1039/c4cy01407c
|View full text |Cite
|
Sign up to set email alerts
|

A novel magnetic palladium catalyst for the mild aerobic oxidation of 5-hydroxymethylfurfural into 2,5-furandicarboxylic acid in water

Abstract: Magnetically separable, graphene oxide-supported palladium nanoparticles showed high catalytic activity for the aerobic oxidation of 5-hydroxymethylfurfural into 2,5-furandicarboxylic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
72
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(74 citation statements)
references
References 43 publications
(40 reference statements)
1
72
0
Order By: Relevance
“…The literature survey for the oxidation of HMF to FDCA indicated that this reaction has been performed using stoichiometric amounts of oxidants and expensive catalytic systems containing noble metals such as Pt [17][18][19][20][21][22], Pd [23][24][25][26], Au [27][28][29][30][31][32], Ru [33], or their alloys [34][35][36][37][38][39][40][41]. In addition, the presence of a base is crucial in order to facilitate the desorption of the resulted acid from the catalytic surface.…”
Section: Introductionmentioning
confidence: 99%
“…The literature survey for the oxidation of HMF to FDCA indicated that this reaction has been performed using stoichiometric amounts of oxidants and expensive catalytic systems containing noble metals such as Pt [17][18][19][20][21][22], Pd [23][24][25][26], Au [27][28][29][30][31][32], Ru [33], or their alloys [34][35][36][37][38][39][40][41]. In addition, the presence of a base is crucial in order to facilitate the desorption of the resulted acid from the catalytic surface.…”
Section: Introductionmentioning
confidence: 99%
“…The oxidation of HMF or other furans to FDCA has been achieved mainly by metal-based catalysis [4][5][6][7]. Yet, the search for an efficient chemical process for converting HMF into valuable building blocks such as FDCA is still ongoing.…”
Section: Introductionmentioning
confidence: 99%
“…Excellent results were also achieved by the oxidation of HMF over C-Fe 3 O 4 -Pd catalyst in air and at room temperature with an appropriate reaction time. More importantly, the catalyst was easily recovered by an external magnet and reused without the loss of its catalytic activity [7]. Actually, epoxy systems have assorted and routinely applications as coating materials, adhesives and composites have dominant application position in contrast to other polymers.…”
Section: Introductionmentioning
confidence: 99%